Child Wanted and When? Fertility Intentions, Wantedness, and Child Survival in Rural Northern Ghana. Issue 3 (5th September 2016) - Bawah, Ayaga A.; Asuming, Patrick O.; Debpuur, Cornelius; Phillips, James F.
Abstract : Panel survey data collected in rural northern Ghana asked women about the "wantedness" status of their children. Parous women were asked whether they wanted more children, while those who had never had a child were asked whether they wanted to have children in the future; those who said that they did not want to have any more children in the future were asked whether they wanted to become pregnant when they last became pregnant and, if so, whether they wanted to become pregnant at the time, or would have preferred to be pregnant earlier or later. This article analyzes longitudinal responses to these questions over a 10‐year period. Birth and survival histories of subsequently born children linked to preference data permit investigation of the question: are "wanted" children more likely to survive than "unwanted" children? Hazard models are estimated to determine whether children born to women who indicated that they did not want to have a child at the time they did, or did not want any more children in the future, have a higher risk of mortality relative to children who were reported wanted at the time of pregnancy. Results show no significant differences in adjusted mortality risks between children who were reported to be wanted and those reported to be unwanted.